2015
DOI: 10.1371/journal.pone.0134864
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Visual Outcomes of Secondary Intraocular Lens Implantation in Children with Congenital Cataracts

Abstract: AimThe aim of this study was to evaluate the long-term visual outcomes and factors affecting visual results in children undergoing secondary intraocular lens (IOL) implantation following primary congenital cataract extraction.MethodsChildren with congenital cataracts who underwent secondary IOL implantation for aphakia at the Eye and ENT Hospital of Fudan University between January 1, 2001, and December 31, 2007, were retrospectively reviewed. One eye was randomly selected in children with bilateral cataracts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
0
18
0
13
Order By: Relevance
“…BCVA was evaluated using the Teller Acuity Card Test (Vistech, Dayton, Ohio, USA) in preverbal children or the Snellen chart or “E” charts in older children. The results were converted to the logarithm of the minimum angle of resolution (LogMAR) for statistical analysis 3 38 . The BCVA was recorded at the last follow-up visit after surgery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BCVA was evaluated using the Teller Acuity Card Test (Vistech, Dayton, Ohio, USA) in preverbal children or the Snellen chart or “E” charts in older children. The results were converted to the logarithm of the minimum angle of resolution (LogMAR) for statistical analysis 3 38 . The BCVA was recorded at the last follow-up visit after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Although visual acuity can be surgically restored in children with CC, there is great variability in visual outcomes following cataract surgery; some children achieve good postoperative visual acuity, whereas others obtain poor visual outcomes. It has been reported that 5.3% (4/76) of eyes achieve a best-corrected visual acuity (BCVA) of greater than 1.0 and that 7.9% (6/76) of eyes achieve a BCVA of less than 0.1 after bilateral cataract extraction and secondary intraocular lens (IOL) implantation 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Parental cooperation was defined according to their compliance for at least 50% of recommended patching hours by asking them at follow-up visits. 12 Partial compliance was considered if parents did not have compliance more than 50% of a day in all periodic follow-ups.…”
Section: Methodsmentioning
confidence: 99%
“…Konjenital kataraktların görülme sıklığı 10000 doğumda 1,2-6 arasında değişmektedir. Okul öncesi çocuklarda körlük nedenlerinin %10'unu oluştururken, yaklaşık % 34'ü de ailesel özellik taşımaktadır (1,(4)(5)(6)(7)(8).…”
Section: Discussionunclassified